Distribution and Thermal Maturity of Devonian Carbonate Reservoir Solid Bitumen in Desheng Area of Guizhong Depression, South China. (15th August 2017) - Hou, Yuguang; Liang, Yaqi; He, Sheng; Liu, Yukun; Fan, Zhiwei; Song, Yingrui
Abstract : The distribution of solid bitumen in the Devonian carbonate reservoir from well Desheng 1, Guizhong Depression, was investigated by optical microscope and hydrocarbon inclusions analysis. Vb and chemical structure indexes measured by bitumen reflectance, laser Raman microprobe (LRM), and Fourier transform infrared spectroscopy (FTIR) were carried out to determine the thermal maturity of solid bitumen. Based on the solid bitumen thermal maturity, the burial and thermal maturity history of Devonian carbonate reservoir were reconstructed by basin modeling. The results indicate that the fractures and fracture-related dissolution pores are the main storage space for the solid bitumen. The equivalent vitrinite reflectance of solid bitumen ranges from 3.42% to 4.43% converted by Vb (%) and LRM. The infrared spectroscopy analysis suggests that there are no aliphatic chains detected in the solid bitumen which is rich in aromatics C=C chains (1431–1440 cm −1 ). The results of Vb (%), LRM, and FTIR analysis demonstrate that the solid bitumen has experienced high temperature and evolved to the residual carbonaceous stage. The thermal evolution of Devonian reservoirs had experienced four stages. The Devonian reservoirs reached the highest reservoir temperature 210–260°C during the second rapid burial-warming stage, which is the main period for the solid bitumen formation.